2019
DOI: 10.1002/aoc.5175
|View full text |Cite
|
Sign up to set email alerts
|

Structural and theoretical studies of the methoxycarbonylation of higher olefins catalysed by (Pyrazolyl‐ethyl)pyridine palladium (II) complexes

Abstract: Reactions of 2-[1-(3,5-dimethylpyrazol-1-yl)ethyl]pyridine (L1) and 2-[1-(3,5diphenylpyrazol-1-yl)ethyl]pyridine (L2) with the [Pd (COD)Cl 2 ] or [Pd (COD)MeCl] produced palladium (II) complexes [Pd(L1)ClMe] (1), [Pd(L1) Cl 2 ] (C2), [Pd(L2)ClMe] (3), and [Pd(L2)Cl 2 ] (4) in quantitative yields. Solid state structures of complexes 1, 3 and 4 established the formation of mononuclear compounds, containing one bidentate ligand unit per metal atom, to give square planar complexes. All the other spectroscopic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…For example, palladium(II) catalysts based on mixed N^N^O(S) (TON of 264) in the methoxycarbonylation reaction. [29,32] While the catalytic activities of the current are comparable with our previous systems, [21,25,30,51] complexes Pd1-Pd5 registered significant improvement with respect to regioselectivity. For instance, while most of our previous reports produced linear and branched products in almost equal quantities, the current complexes afforded up to 75% of the linear esters in the methoxycarbonylation of 1-hexene.…”
Section: The Influence Of Complex Structuresupporting
confidence: 78%
See 2 more Smart Citations
“…For example, palladium(II) catalysts based on mixed N^N^O(S) (TON of 264) in the methoxycarbonylation reaction. [29,32] While the catalytic activities of the current are comparable with our previous systems, [21,25,30,51] complexes Pd1-Pd5 registered significant improvement with respect to regioselectivity. For instance, while most of our previous reports produced linear and branched products in almost equal quantities, the current complexes afforded up to 75% of the linear esters in the methoxycarbonylation of 1-hexene.…”
Section: The Influence Of Complex Structuresupporting
confidence: 78%
“…These results are in good agreements with previous reports and have been associated with steric and electronic contributions from various alkenes. [ 22,25,30,51 ] The superior percentage yields recorded for styrene (>99%) is normal and is attributed to the resultant benzylic palladium(II) intermediate, which is a more active as compared to alkyl palladium(II) species, in aliphatic alkenes. [ 56 ] The identity of the olefin substrate also controlled the type of the ester products yielded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that 1 H NMR signals of thiazine and thiazoline of all complexes are in general shifted to higher frequencies with respect to their free ligands. This also occurs for pyrazole ring signals for PdPzTn, PdPzTz, and PdDMPzTn, while the signals of complexes with phenyl substituents are slightly shifted to lower frequencies, probably due to the presence of aromatic groups which help with the redistribution of electronic density loss [ 26 , 27 ]. Therefore, it can be concluded that the ligands are coordinated to palladium in DMF solution for PdPzTn, PdPzTz, PdDPhPzTn, and PdDPhPzTz and in DMSO solution for PdDMPzTn.…”
Section: Resultsmentioning
confidence: 99%